2016
DOI: 10.1016/j.bonr.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Iroquois homeobox transcription factors 3 and 5 in osteoblasts disrupts cranial mineralization

Abstract: Cranial malformations are a significant cause of perinatal morbidity and mortality. Iroquois homeobox transcription factors (IRX) are expressed early in bone tissue formation and facilitate patterning and mineralization of the skeleton. Mice lacking Irx5 appear grossly normal, suggesting that redundancy within the Iroquois family. However, global loss of both Irx3 and Irx5 in mice leads to significant skeletal malformations and embryonic lethality from cardiac defects. Here, we study the bone-specific function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…S8 B ). Because IRX5 is required for osteoblast differentiation in endochondral and membranous bones, ( 31 ) this result could be due to the complete absence of Irx5 in both HC derived and non–HC‐derived lineages in the mutants. Interestingly, the percentages of non–HC‐derived adipocytes (Perilipin + /Td − cells) were comparable between mutants and controls (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S8 B ). Because IRX5 is required for osteoblast differentiation in endochondral and membranous bones, ( 31 ) this result could be due to the complete absence of Irx5 in both HC derived and non–HC‐derived lineages in the mutants. Interestingly, the percentages of non–HC‐derived adipocytes (Perilipin + /Td − cells) were comparable between mutants and controls (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(29,30) Notably, osteopenia was observed in 3-week-old to 4-week-old mice with osteoblast-specific removal of Irx3/5. (31) IRX3 and IRX5 are also implicated in regulating the balance between beige adipose tissue (BAT) and white adipose tissue (WAT). Irx3 null mice and transgenic mice expressing dominant-negative forms of IRX3 in adipocytes displayed resistance to weight gain and greater energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…On the distal RE, when allele at rs11609649 was changed to the effective allele, there were a gain of motif “PH0082.1_Irx2/Jaspar” and a loss of motif FOXM1_1/encode. These two motifs corresponded to IRX3 and FOXM1 respectively, which were highly expressed in CNCC (FPKM of IRX3 68.12, FOXM1 49.03) and played roles in development of CNCC and derivatives 46 , 47 (Fig. 4e , Supplementary Data 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that Rln1 plays a functional role in osteoblastic differentiation in cultured cells [48], suggesting its potential role in bone development. Irx5 was relatively highly expressed during osteoblast differentiation (S2 Table), and previous studies have shown that combined deletion of Irx3 and Irx5 leads to significant skeletal limb malformations [49] and mimics human iroquois homeobox 5 (IRX5) mutation-induced defective craniofacial development in mice [50, 51]. However, Irx5 mutation alone leads to viable mice with normal fertility, although they are slightly smaller than their wild-type counterparts [52, 53], leaving an open question of whether Irx5 is involved in bone development.…”
Section: Resultsmentioning
confidence: 99%